Livelihood Diversification in Rainfed Areas of Telangana State: Evidence from Household Level Survey (Indian Journal of Extension Education, 2024)
Farmers in rainfed agriculture participate in both on-farm and off-farm activities to reduce risks from weather shocks, low farm fragmentation, low soil productivity, and frequent droughts and floods. Dependence on farm revenue alone proved difficult and risky. The study was conducted in 2022 to determine patterns and a livelihood diversification index at the household level for various farm sizes producing the chickpea crop. Primary data were acquired from 80 randomly selected farmer respondents in four mandals of Kamareddy district in Telangana State. Descriptive statistics were applied to characterize the sample households’ demographic, social, and economic factors. The livelihood diversification index was estimated using the Simpson diversity index at the household level. The data revealed that small and marginal farmers have very high diversification levels, while medium and large farmers have high diversification levels. The percentage share of on farm income stands highest for large farmers and lowest for marginal farmers and vice versa about non-farm activity. Regression analysis indicated education, farm size, total on-farm income, and net returns from pulse crops were significant determinants for diversification. The study further suggests that government support needs to focus on the provision of incentives for diversification at both on-farm and non-farm levels.